The Influence Of Influencer Credibility, Brand Image, Brand Trust, And Review Content On Purchase Decisions Of Somethinc Products On Tokopedia - Indah Pratiwi; Andri Soemitra; Nurbaiti Nurbaiti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The business world is becoming increasingly competitive in terms of both goods and services due to the rapid development of technology and information in the Industry 4.0 era. With more and more local cosmetic brands emerging, the development of beauty products is also growing. One local company that has found success in the skincare sector is Somethinc. To better understand how consumers choose products on Tokopedia, this study will examine four independent variables: credibility influencers, brand image, brand trust, and content reviews. Using the SPSS 29 program, this research methodology is quantitative. A total of 100 subjects were included in the 96.04 sample obtained through the incidental sampling technique. Based on the simultaneous test results, brand image, brand trust, credibility influencers, and review content have a major influence on consumer purchasing decisions. The calculated f value is 52.617 with a significance level of 0.001 0.05, in accordance with the findings of the ANOVA test, where the calculated f value is 52.617 2.47 with (df1=5-1=4 and df2=n-5=95).